Readings of the enlightened Sarmatian traveller in the light of the catalogue of books read by Seweryn Rzewuski during his journey (1778) - Kucharski, Adam (Folia Toruniensia, 2017)
The level of knowledge about foreign travels of inhabitants of the Polish-Lithuania Commonwealth has risen owing to historical sources published both in the form of critical source editions and scientific studies. One of the most interesting documents which allows us to learn about the role of the book and the development of reading culture among Early Modern travellers is the catalogue of books which Seweryn Rzewuski, a Polish politician and magnate, took with him during his journey in 1778. The article presents the politician not as one of the leaders of the Targowica Confederation, but from a slightly different angle. The archival inventory of the travel library of Rzewuski constitutes the unique source of its kind; that is why, it is worth examining only to show the variety of interests of this traveller. Presenting his political views and the conscious selection of books to read, he seems to have a complex personality standing on the border between the mentality of a Sarmatian pilgrim and an enlightened traveller.